2006
DOI: 10.1002/elps.200500808
|View full text |Cite
|
Sign up to set email alerts
|

Protein tryptic digests analyzed by carrier ampholyte‐based capillary electrophoresis coupled to ESI‐MS

Abstract: In this study, narrow pH cuts of carrier ampholytes have been used as buffers in CE for the analysis of protein tryptic digests. Their low conductivity allows very efficient separations under high electric field strength without inducing any significant Joule heating. In this study, the capabilities of narrow pH cuts of carrier ampholytes for the separation of protein tryptic digests have been assessed. Three proteins of different molecular masses have been studied: cytochrome C (horse heart), beta-lactoglobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…As a consequence, NC have very low conductivity and very low ionic strength while maintaining a satisfying buffering capacity [28]. These properties make them excellent BGEs for CZE [29][30][31][32]. We have also previously shown that added to commercial carrier ampholyte mixtures they could improve CIEF resolution [33].…”
Section: Introductionmentioning
confidence: 92%
“…As a consequence, NC have very low conductivity and very low ionic strength while maintaining a satisfying buffering capacity [28]. These properties make them excellent BGEs for CZE [29][30][31][32]. We have also previously shown that added to commercial carrier ampholyte mixtures they could improve CIEF resolution [33].…”
Section: Introductionmentioning
confidence: 92%
“…25 In this situation, the bound cysteine residues had little influence on Ag NCs. However, when trypsin was introduced, it digested Cyt c to small peptides, 26 and released free cysteine residues, which could decrease the fluorescence intensity of Ag NCs. 27 This explains why the fluorescence intensity could not restore to its initial value.…”
Section: Fluorescence Assay For Trypsinmentioning
confidence: 99%
“…In this last case, ultranarrow pH cuts (encompassing typically 0.1 pH units) are used, thus the method is implemented not as a focusing technique, but in a zone electrophoretic approach in a capillary format (CZE) [14][15][16]. Interestingly, this new methodology is exploited not only for proteins, but for peptide separations as well, by interfacing the capillary outlet directly with an MS instrument [17].…”
Section: Introductionmentioning
confidence: 99%